Three siblings with familial non-medullary thyroid carcinoma: a case series. (December 2016) - Rashid, Muhammad; Haq, Naeemul; Farooq, Saad; Kiran, Zareen; Siddique, Sabeeh; Pervez, Shahid; Islam, Najmul
Abstract Background In 2015, thyroid carcinoma affected approximately 63, 000 people in the USA, yet it remains one of the most treatable cancers. It is mainly classified into medullary and non-medullary types. Conventionally, medullary carcinoma was associated with heritability but increasing reports have now begun to associate non-medullary thyroid carcinoma with a genetic predisposition as well. It is important to identify a possible familial association in patients diagnosed with non-medullary thyroid carcinoma because these cancers behave more destructively than would otherwise be expected. Therefore, it is important to aggressively manage such patients and screening of close relatives might be justified. Our case series presents a diagnosis of familial, non-syndromic, non-medullary carcinoma of the thyroid gland in three brothers diagnosed over a span of 6 years. Case presentations We report the history, signs and symptoms, laboratory results, imaging, and histopathology of the thyroid gland of three Pakistani brothers of 58 years, 55 years, and 52 years from Sindh with non-medullary thyroid carcinoma. Only Patients 1 and 3 had active complaints of swelling and pruritus, respectively, whereas Patient 2 was asymptomatic. Patients 2 and 3 had advanced disease at presentation with lymph node metastasis. All patients underwent a total thyroidectomy with Patients 2 and 3 requiring a neck dissection as well. No previous exposure to radiation was present in any of the patients. Their mother had died from adrenal carcinoma but also had a swelling in the front of her neck which was never investigated. All patients remained stable at follow-up. Conclusions Non-medullary thyroid carcinoma is classically considered a sporadic condition. Our case report emphasizes a high index of suspicion, a detailed family history, and screening of first degree relatives when evaluating patients with non-medullary thyroid carcinoma to rule out familial cases which might behave more aggressively.